Three‐Component Perfluoroalkylvinylation of Alkenes Enabled by Dual DBU/Fe Catalysis. Issue 8 (14th December 2022) - Tang, Lin; Lv, Ge; Cheng, Ruimin; Yang, Fang; Zhou, Qiuju
Abstract: Herein, a simple and efficient strategy that involves dual 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU)/iron‐catalyzed alkene perfluoroalkylvinylation by using perfluoroalkyl iodides and 2‐aminonaphthalene‐1, 4‐diones as coupling partners is demonstrated. In terms of the developed catalytic system, various styrenes and aliphatic alkenes are well‐tolerated, leading to the accurate preparation of perfluoroalkyl‐containing 2‐aminonaphthalene‐1, 4‐diones in excellent regioselectivity. Moreover, the protocol can be readily applied in late‐stage modifications of natural products and pharmaceuticals. The title reactions are featured by easily accessible and inexpensive catalysts and substrates, broad substrate applicability, and mild reaction conditions. Mechanistic investigations reveal a tandem C−I cleavable alkylation and C−C vinylation enabled by cooperative DBU/iron catalysis. Abstract : The first example of an efficient DBU/iron co‐catalyzed three‐component perfluoroalkylvinylation of alkenes has been reported through a radical process under mild conditions.